Container Image Schema in Arabic Quotations on Telegram Channel ‘عطر الورد’: A Cognitive Semantic Analysis - Nuriyah, Siti Ainun; Lukman, Fahmy (Universitas Yudharta Pasuruan, 2025)
This study aims to analyze the use of container image schemas in Arabic quotations on the Telegram channel عطر الورد ‘Iṭru al-Ward’. The method used is descriptive qualitative with a cognitive semantic approach. The research data were taken from Arabic quotations on the Telegram channel عطر الورد ‘Iṭru al-Ward’ uploaded in October 2024. The data were analyzed based on the theoretical framework of conceptual metaphor and image schema. The research results show that there are 16 container image schemas formed from two types of conceptual metaphors, namely 13 ontological metaphors and 3 structural metaphors. The container image schemas are classified into four categories, namely 7 containment, 5 full-empty, 3 content, and 1 in-out. Meanwhile, the surface image schema was not found in this research data. The research findings indicate that Arab society conceptualizes emotional and spiritual conditions through container metaphors, where the heart, soul, and life are understood as spaces that can be filled, emptied, or traversed by various feelings and experiences. This study can contribute to Arabic language learners in understanding abstract metaphorical meanings through a cognitive semantic approach.